The associations between current and anticipatory weight-related shame and flourishing in adolescent girls in sport - Lucibello, Kristen M.; Zeitoun, Tara; Brown, David M.; Pila, Eva; Sabiston, Catherine M. (Frontiers in Psychology, 2025)
Flourishing (i.e., positive mental health reflecting positive social relationships and sense of purpose and optimism) is important for experiencing growth, resilience, and functioning – especially in sport. Factors that may limit or potentiate the experience of flourishing in sport need to be understood. For girls involved in sport, weight-related shame may be a critical factor limiting the potential to flourish. The purpose of the present study was to explore current and anticipatory weight-related shame in association with flourishing among adolescent girls. Participants were Canadian girl athletes (N = 189) aged 13 to 18 years old (M = 15.93, SD = 1.22) who had previous or current involvement in organized sport. Girls completed a self-report survey where they reported their current and anticipatory (weight gain or loss) shame and flourishing. A Path model was tested in MPlus. Higher current weight shame [Estimate = −0.41, SE = 0.07, p < 0.01] and anticipatory weight loss shame [Estimate = −0.13,. SE = 0.07, p = 0.03], were associated with lower flourishing. Anticipatory weight gain shame was not associated with lower flourishing. These results suggest efforts are needed to disconnect the emotion of shame from weight change to foster positive psychological outcomes, such as flourishing, in sport contexts.